Improvement of Student Learning Outcomes Using E-Worksheets Assisted Live Worksheets on Basic Chemistry Laws Material - Arifianti, Dwi; Yanuardani, Ayu; Khasanah, Maulidia Uswatun; Kusumaningrum, Yesika Dewi; Ayunin, Khurota; Azizah, Utiya; Asih, Dian; Rahadityo, Purwo (Jurnal Pijar Mipa, 2025)
This study investigates the improvement of student learning outcomes using e-worksheet media with Live Worksheets. Conducted as Classroom Action Research (CAR), it involved 38 students from class X-7 at SMA Negeri 18 Surabaya. Data collection included observation techniques and learning outcome tests aimed at assessing teacher and student activities. The observation data were analyzed using a percentage formula for relevant activities over two meetings. Learning outcome tests measured improvements after cycles I and II, analyzed for the percentage of classical completeness in learning outcomes. Results indicated that teacher activity increased from 91% in cycle I to 100% in cycle II, while student activity rose from 79% to 89%, which falls into the very practical category. Additionally, learning outcomes improved significantly, increasing from 50% before the intervention to 79% in cycle I and 89% in cycle II, which is ≥75%. These findings demonstrate the effectiveness of e-worksheet media in improving educational engagement and achievement. The study concludes that technology-based learning innovations can effectively address educational challenges and recommends further development of interactive learning tools across various subjects and educational levels.